(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
This study examined the level of achievement motivation among government and private school children in Hazaribag and about the factors which are the causes of the difference in the level of achievement motivation of students of the factor are Gender, place of residence, Type of school, and occupation of parents. The literature on Achievement motivation has clarified that these factors play an important role in the level of achievement motivation.This study aimed to know the level of achievement motivation among the secondary school’s children of the District. The tool which was used in the study is highly reliable. Dev Mohan achievement motivation (n-ACH) by Pratibha Deo & Asha Mohan has been used; sample of students was selected from both types of schools private and government of Hazaribag. Out of which according to the 4 factors difference was calculated, mean, S.D and t-value was calculated. The level of achievement motivation was calculated. The result showed that these was no difference in the level of achievement motivation due to gender and place of residence, but there was difference in the level of achievement motivation due to the type of school and occupation of the parents.Thus this study is more important in increasing program to enhance achievement motivation which is a new concept and should be implemented in the field of education. This will increase zeal for success in the students and will reduce their fear of failure. Today the need and lust for being successful is increasing hence for proper guidance and for fulfilling the demands of the time the concept of achievement motivation should be applied in all stages of education.